Chronic neurotrophin delivery promotes ectopic neurite growth from the spiral ganglion of deafened cochleae without compromising the spatial selectivity of cochlear implants. Issue 12 (19th June 2013) - Landry, Thomas G.; Fallon, James B.; Wise, Andrew K.; Shepherd, Robert K.
ABSTRACT Cochlear implants restore hearing cues in the severe–profoundly deaf by electrically stimulating spiral ganglion neurons (SGNs). However, SGNs degenerate following loss of cochlear hair cells, due at least in part to a reduction in the endogenous neurotrophin (NT) supply, normally provided by hair cells and supporting cells of the organ of Corti. Delivering exogenous NTs to the cochlea can rescue SGNs from degeneration and can also promote the ectopic growth of SGN neurites. This resprouting may disrupt the cochleotopic organization upon which cochlear implants rely to impart pitch cues. Using retrograde labeling and confocal imaging of SGNs, we determined the extent of neurite growth following 28 days of exogenous NT treatment in deafened guinea pigs with and without chronic electrical stimulation (ES). On completion of this treatment, we measured the spread of neural activation to intracochlear ES by recording neural responses across the cochleotopically organized inferior colliculus using multichannel recording techniques. Although NT treatment significantly increased both the length and the lateral extent of growth of neurites along the cochlea compared with deafened controls, these anatomical changes did not affect the spread of neural activation when examined immediately after 28 days of NT treatment. NT treatment did, however, result in lower excitation thresholds compared with deafened controls. These data support the application of NTs for improved clinical outcomes for cochlear implant patients. J. Comp. Neurol. 521:2818–2832, 2013. © 2013 Wiley Periodicals, Inc.